EFFECTIVENESS OF THE STUNTING REDUCTION ACCELERATION PROGRAM IN GUNUNGSITOLI CITY - Eldad Chalis Natha Nias Ndruru; Andi Fitra Suloi; Arga Ramadhana (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
Stunting of toddlers is a major nutritional problem in Indonesia. In Gunungsitoli City, the prevalence of stunting in 2021 was recorded at 26.3%. This study aims to determine the effectiveness of the stunting reduction acceleration program in Gunungsitoli City, using Budiani (2009) theoretical indicators consisting of the dimensions of program target accuracy, program socialization, program goal achievement, and program monitoring. This study uses a qualitative approach; data is collected through interviews with key and supporting informants and qualitative data analysis. The results of the study show that the obstacles in the effectiveness of the stunting reduction acceleration program in Gunungsitoli City are based on indicators of the accuracy of program goals, program socialization, achievement of program goals, and program monitoring and can be concluded that it has been implemented effectively, where the reduction of stunting rates in Gunungsitoli City as one of the goals of the integrated stunting reduction acceleration program. Communication between agencies must be further improved so that the effectiveness of the stunting program is as expected.